2013
DOI: 10.1007/s00403-013-1404-z
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic keratinocytes prime neutrophils for an overproduction of superoxide anions

Abstract: Psoriatic plaques result from an abnormal proliferation of keratinocytes associated with the local presence of T lymphocytes and neutrophils. The exact role of neutrophils in psoriatic lesions remains unclear. The present investigation was aimed at deciphering the capacity of psoriatic keratinocytes to alter in vitro functions of neutrophils. Blood neutrophils from healthy donors were incubated with psoriatic (PK) or healthy keratinocytes (HK) with and without IL-2-activated healthy T lymphocytes. The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 86 publications
0
24
0
2
Order By: Relevance
“…The analysis of gene expression alone is not sufficient to resolve this issue, but quantitative analyses of gene expression can at least provide objective insights [7]. Our analysis of genes near susceptibility loci from psoriasis GWAS studies lends support to multiple cell types, including T-cells, but above all our findings bolster support for neutrophils as participants in pathogenetic disease mechanisms [24,49,54,55,60]. We expect that this conclusion can be sharpened by future work, based upon the identification of new psoriasis susceptibility loci, new experimental evidence, generation of new datasets for evaluating cell type-specific expression, and continued development of bioinformatic analysis protocols.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The analysis of gene expression alone is not sufficient to resolve this issue, but quantitative analyses of gene expression can at least provide objective insights [7]. Our analysis of genes near susceptibility loci from psoriasis GWAS studies lends support to multiple cell types, including T-cells, but above all our findings bolster support for neutrophils as participants in pathogenetic disease mechanisms [24,49,54,55,60]. We expect that this conclusion can be sharpened by future work, based upon the identification of new psoriasis susceptibility loci, new experimental evidence, generation of new datasets for evaluating cell type-specific expression, and continued development of bioinformatic analysis protocols.…”
Section: Discussionmentioning
confidence: 74%
“…Neutrophils also represent a source of cytokines demonstrated to drive lesion development, such as IL-17A, and indeed one study indicated that IL-17A(+) neutrophils are more abundant in lesions than IL-17A(+) T-cells [54]. Such epidermal neutrophils generate reactive oxygen species such as superoxide anion, leading to tissue damage and possible hyper-activation of innate defense mechanisms [55]. Neutrophils also interact with other cell types, such as KCs, T-cells and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the redox state in psoriasis, there are increasing studies that showed higher levels of oxidative stress markers in psoriatic subjects, such as nitric oxide 63 , superoxide dismutase, catalase 64 , superoxide anions 65 and peroxiredoxin 2 (refs 66,67). A recent report also showed significantly higher H 2 O 2 and Nox activity in white blood cells of psoriatic patients compared with controls 68 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recently conducted studies showed that the blood neutrophil counts are increasing in patients with psoriasis and amount of superoxide anions are increased in these neutrophils [16, 17]. …”
Section: Discussionmentioning
confidence: 99%